2020
DOI: 10.1093/mnras/staa746
|View full text |Cite
|
Sign up to set email alerts
|

The role of galaxies and AGN in reionizing the IGM – III. IGM–galaxy cross-correlations at z ∼ 6 from eight quasar fields with DEIMOS and MUSE

Abstract: We present improved results of the measurement of the correlation between galaxies and the intergalactic medium (IGM) transmission at the end of reionisation. We have gathered a sample of 13 spectroscopically confirmed Lyman-break galaxies (LBGs) and 21 Lyman-α emitters (LAEs) at angular separations 20 θ 10 (∼ 0.1 − 4 pMpc at z ∼ 6) from the sightlines to 8 background z 6 quasars. We report for the first time the detection of an excess of Lyman-α transmission spikes at ∼ 10 − 60 cMpc from LAEs (3.6σ) and LBGs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 117 publications
1
25
0
1
Order By: Relevance
“…This test that was originally proposed and observationally performed by Kakiichi et al (2018). Subsequently, additional observations, as well as a refinement of the approach itself, have been provided by Meyer et al (2019) and Meyer et al (2020). In particular, Meyer et al (2019) have shown that at 4.5 z 6.3 the transmitted flux displays a broad peak at intermediate distances to galaxies 10 r/[cMpc/h] 30, which has been interpreted as a proximity effect of the latter.…”
Section: The Igm -Galaxy Connectionmentioning
confidence: 97%
See 1 more Smart Citation
“…This test that was originally proposed and observationally performed by Kakiichi et al (2018). Subsequently, additional observations, as well as a refinement of the approach itself, have been provided by Meyer et al (2019) and Meyer et al (2020). In particular, Meyer et al (2019) have shown that at 4.5 z 6.3 the transmitted flux displays a broad peak at intermediate distances to galaxies 10 r/[cMpc/h] 30, which has been interpreted as a proximity effect of the latter.…”
Section: The Igm -Galaxy Connectionmentioning
confidence: 97%
“…We begin providing a synthetic version of the observations of Kakiichi et al (2018), Meyer et al (2019) and Meyer et al (2020) in Fig. 14, where we show the transmitted (normalized) flux at z = 5.5 in a random sightline through the thesan-1 box (solid black line and left vertical scale).…”
Section: The Igm -Galaxy Connectionmentioning
confidence: 99%
“…In this regard, star-forming complexes (<200 pc size) at high redshift and high mass star clusters (e.g., <30 pc radius) will be accessed and compared to local similar star-forming regions, allowing for detailed studies of (1) star-formation modes (e.g., location and spectral signatures of massive stars); (2) the presence of high-ionization lines and the related ionization photon production efficiency (e.g., Bouwens et al 2016;Amorín et al 2017;Senchyna et al 2017Senchyna et al , 2019Senchyna et al , 2020aChevallard et al 2018;Lam et al 2019); and (3) interactions with the surrounding medium (feedback), including the capacity to modulate the opacity of the interstellar medium to ionizing radiation up to circumgalactic scales (which is key for the escape of ionizing photons, e.g., Erb 2015;Grazian et al 2017;Vanzella et al 2020a;He et al 2020). These are all key ingredients in the pursuit of answers to two of the most pressing questions in current observational cosmology: (i) what sources reionized the Universe (e.g., Robertson et al 2015;Giallongo et al 2015;Meyer et al 2020;Eide et al 2020;Dayal et al 2020); (ii) how globular clusters formed (Renzini et al 2015;Renzini 2017;Pfeffer et al 2018Pfeffer et al , 2019Calura et al 2019;Bastian & Lardo 2018); (iii) and how these two questions might be related to each other (e.g., Ricotti 2002;Schaerer & Charbonnel 2011;Katz & Ricotti 2013;Boylan-Kolchin 2018;Ma et al 2020;He et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Middle: similar to the left panel, but integrating down to different MUV. Right: the black curve shows fescξion in the fiducial model compared to Lyα forest cross-correlation measurements at z ∼ 5-6 (Meyer et al 2019(Meyer et al , 2020 shown by the horizontal bands and hashes.…”
Section: Implications For Reionization-epoch Galaxiesmentioning
confidence: 99%